1995
DOI: 10.1144/gsl.sp.1995.086.01.14
|View full text |Cite
|
Sign up to set email alerts
|

Petroleum geochemistry of the Haltenbanken, Norwegian continental shelf

Abstract: Thirty-three oil/condensate samples, representing most of the known petroleum accumulations in the Haltenbanken region, were analysed by a comprehensive geochemical scheme to determine possible genetic relationships. The organic geochemistry of the samples is comparatively invariate if one excludes the characteristics attributed to maturity differences and phase-induced fractionation. On this basis, in a gross sense, the C 10+ fractions of most of the petroleum samples are suggested to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
68
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(72 citation statements)
references
References 67 publications
4
68
0
Order By: Relevance
“…Dahl and Speers, 1986;Karlsen et al, 1995;Leythaeuser and Rückheim, 1989;Tissot and Welte, 1984). A number of studies, devoted to understanding the reasons and consequences of diversities in petroleum composition, have already been undertaken long ago (Bailey et al, 1973a;Bailey et al, 1973b;Dahl and Speers, 1986;Espach and Fry, 1951;Evans et al, 1971;Hirschberg, 1988;Hunt, 1979;Justwan and Dahl, 2005;Karlsen et al, 1995;Karlsen and Skeie, 2006;Milner et al, 1977;Sage and Lacey, 1939;Tissot and Welte, 1984;Tyson, 1995). These studies have revealed that the factors that cause heterogeneities in petroleum composition in reservoirs can roughly be related to 1) variations in source rock organic facies and source rock maturity and 2) secondary alteration processes.…”
Section: 2mentioning
confidence: 99%
See 1 more Smart Citation
“…Dahl and Speers, 1986;Karlsen et al, 1995;Leythaeuser and Rückheim, 1989;Tissot and Welte, 1984). A number of studies, devoted to understanding the reasons and consequences of diversities in petroleum composition, have already been undertaken long ago (Bailey et al, 1973a;Bailey et al, 1973b;Dahl and Speers, 1986;Espach and Fry, 1951;Evans et al, 1971;Hirschberg, 1988;Hunt, 1979;Justwan and Dahl, 2005;Karlsen et al, 1995;Karlsen and Skeie, 2006;Milner et al, 1977;Sage and Lacey, 1939;Tissot and Welte, 1984;Tyson, 1995). These studies have revealed that the factors that cause heterogeneities in petroleum composition in reservoirs can roughly be related to 1) variations in source rock organic facies and source rock maturity and 2) secondary alteration processes.…”
Section: 2mentioning
confidence: 99%
“…<2 km), where the temperature is not more than about 70-80 °C (cf. Ahsan et al, 1997;Karlsen et al, 1995;Tissot et al, 1974). Furthermore, we noticed minor to moderate levels of biodegradation in some of the migrated petroleum extracts from Svalbard (Paper 3) and of the oil samples from the Barents Sea (Paper 5) which have also been affected by uplift events, erosions and glaciation during the Cenozoic (Ohm et al, 2008).…”
mentioning
confidence: 99%
“…3,4), showing a relatively wide range as has also been observed on the Norwegian Continental Shelf (cf. Karlsen et al, 1995).…”
Section: Saturated Hydrocarbon Maturity Parametersmentioning
confidence: 99%
“…Lewan (1984) reported that V/ (V + Ni) ratio is negatively correlated with the even predominance of n-alkanes and the Pr/Ph ratio, but it is positively correlated with the Ph/nC 18 ratio, which infers marine organic matter input. Nickel, Cobalt, Strontium, Silver and Bismuth have been found to correlate positively with the absolute amount of heavy n-alkanes in the petroleums, as these elements are relatively more abundant in parafinic petroleum (Karlsen et al, 1995). Enriched V and Ni concentrations greater than 100 ppm are observed in bitumens that are associated with Type II and Type I kerogens.…”
Section: Introductionmentioning
confidence: 99%
“…Classification of crude oils into families helps to locate hydrocarbons in explored areas and different stratigraphic units of the basin. It is now known that organic geochemistry is also very useful in petroleum production (Karlsen et al, 1995;Larter and Aplin, 1995).…”
Section: Introductionmentioning
confidence: 99%